ISSUES OF THE FORMATION OF THE PROFESSIONAL COMPONENT OF FUTURE TEACHERS (ON THE EXAMPLE OF THE SCIENCE OF PHYSICAL CULTURE) - Saruxanov Arsen Albertovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will reveal about the development of professional training of future teachers of Physical Culture, the technology for the formation of their educational activities, ways to form pedogogogic competence, forming knowledge, skills, skills in them.